Nuit électrique : atmosphères lumineuses à Montréal au XIXe siècle - Téllez Niemeyer, Valeria (RACAR : Revue d'art canadienne / Canadian Art Review, 2020)
In Montréal, the first public demonstration of electric lighting took place in 1879, on the Champ-de-Mars, and was coordinated with a military exercise in honour of Queen Victoria's birthday. At the end of the nineteenth century, modes of experiencing the urban environment by night changed through a series of public demonstrations. These events were ephemeral spectacles designed to expose city dwellers to the unusual effects of electric light. These early experiences with electric light gave rise to new forms of subjectivity that would later be embodied in the everyday spaces of cities. To better understand the impact of electric lighting on the constitution of modern public spaces in Montréal, this article examines the performative nature of the first demonstration in the city in 1879, the role of the main actors involved, and how it was visually represented and disseminated in the press.